Designing Website-Based Library Information System Services in Mts Aisyiyah Binjai - Naufal, Jimmy; Abdul Khaliq (Bahasa Indonesia, 2026)
The school library plays an important role in supporting learning activities. However, library management at MTs Aisyiyah Binjai is still conducted manually, resulting in several problems such as unorganized book data records, slow borrowing and returning processes, and difficulties in generating library reports. This study aims to design a web-based library information system service to support more effective and efficient library data management. The research methods used include observation, interviews, and literature studies to collect data and identify system requirements. The designed system provides features for managing book data, member data, borrowing and returning transactions, and automatic library report generation. The results of this system design are expected to improve library service quality, accelerate administrative processes, and reduce data recording errors. With the implementation of a web-based library information system, the school is expected to manage the library in a more structured manner and support the improvement of students’ reading interest at MTs Aisyiyah Binjai.